TEACHERS’ CREATIVITY IN TRANSFORMING THE MANDATED CURRICULUM INTO A LINGUISTICALLY AND CULTURALLY DIVERSE PEDAGOGICAL PRACTICE - Joko Nurkamto (Proceedings of ISELT FBS Universitas Negeri Padang, 2016)
English language teaching in high schools in Indonesia is carried out based on a nationally compiled curriculum which tends to be standardized and prescriptive – one for all (Widodo, 2016). In reality, the situation in which English is taught and learned is highly complex, due to the interaction of a number of variables, such as political, economic, and geographical factors, as well as the school, the teachers, and the students (Richards, 2002). Therefore, in order to teach successfully, the teacher, as the implementer of the curriculum, needs to interpret this policy creatively in accordance with the situation and context in the field. According to Matsumoto (2009: 160), creativity is “the capacity to produce new art, ideas, techniques, or other products which are useful, aesthetically appealing, meaningful, and correct within a particular field.” In this paper, I will explain the different forms of the teacher’s creativity in teacahing -- the knowledge and skills of the teacher in selecting and applying the appropriate teaching strategies for transforming the lesson (Huizinga, Handlezalts, Nieveen, and Voogt, 2013). In addition to broadening our understanding of the concept of creativity in the teaching of the English language, it is also hoped that this paper will provide input for teachers in the implementation of their pedagogical duties in the field.